SIMBOLISME DALAM PESTA DALOK SUKU UUD DANUM: Perspektif Hermeneutika Paul Ricoeur - Trio Kurniawan (Litbang STFT Widya Sasana Malang, 2018)
The feast of Dalok is the highlight of the feast in the series of death-rites performed by Dayak Uud Danum’s tribe in Serawai, District of Sintang, West Borneo. It is the biggest feast celebrated by this tribe. There are plenty of Symbols found in the rites, and they are picturing the relationship among the human beings and also between the people and The Supreme Being, Tahala’. These Symbols are tied each other very closely like a knot. The author of this article is using Paul Ricoeur’s hermeneutics to reread and reveal the meaning of symbolical knots which are acceptable to the public. Pesta Dalok adalah puncak dari rangkaian upacara kematian dalam suku Dayak Uud Danum di Serawai, Kab. Sintang, Kalimantan Barat. Pesta Dalok menjadi pesta terbesar yang dilaksanakan oleh suku ini. Ada begitu banyak simbol dalam ritus-ritus di pesta ini dan semuanya menggambarkan relasi antara sesama manusia maupun antar manusia dengan Realitas Tertinggi, Tahala’. Simbol-simbol ini saling berhubungan dengan sangat erat ibarat sebuah simpul. Penulis menggunakan hermeneutika Paul Ricoeur untuk membaca ulang dan membuka makna dari simpul-simpul simbolik yang dapat diterima oleh masyarakat.